The State of Ceara in Brazil is a Role Model for Reducing Learning Poverty - Loureiro, Andre; Cruz, Louisee; Lautharte, Ildo; Evans, David K. (World Bank, Washington, DC, 2020)
This report presents the case of the state of Ceara in Brazil that overcame adverse socioeconomic conditions to substantially improve education outcomes with efficient use of resources. Despite having the 5th lowest GDP per capita among the 26 Brazilian states, the 9-million-inhabitant state of Ceara has experienced the largest increase in the national education quality index in both primary and lower secondary education since 2005, with 10 municipalities of Ceara being among the top 20 national ranking, including Sobral which has the highest score. The state of Ceara pioneered the use of results-based financing as part of a comprehensive education reform program that among other elements included strong support to its municipalities to achieve universal literacy by the end of grade 2. The reforms allowed the state to considerably improve learning levels of students in primary and lower secondary education with a high level of efficiency in the use of resources. The main aspects of the reforms are presented and discussed.